Artificial Intelligence in Al-Ghazali's Perspective: Bridging the Concept of Nafs and Machine - Ningrum, Hazizah Mutiara Cahaya; Mualim, Ali Nur; Sudarman, Sudarman; Bedi, Fisman (Islamic Thought Review, 2024)
The rapid development of artificial intelligence (AI) has sparked questions about the limits and potential of AI in mimicking human cognitive abilities. This research aims to bridge the concept of nafs (soul) in Al-Ghazali’s thought with the development of modern AI. This research uses a comparative method with a qualitative approach. Data were analyzed using content analysis techniques to identify similarities and differences between the concept of nafs nathiqah (reason) according to Al-Ghazali and AI. The focus of the analysis includes the potential, limitations, and ethical implications of the two concepts. Al-Ghazali emphasized the importance of reason in acquiring knowledge and developing technology. However, Al-Ghazali also realized the limitations of human reason, namely its inability to fully understand the nature of reality. AI, although capable of mimicking some aspects of the nafs nathiqah, still has fundamental differences. AI operates based on algorithms and data, while nafs nathiqah involves consciousness, intuition, and the ability to understand meaning. AI has great potential to improve the quality of human life, but it needs to be developed and used ethically and responsibly. Al-Ghazali’s thoughts on nafs can provide insights in understanding the potential and limitations of AI, as well as the ethical implications of its use.